Contamination of fish in important fishing grounds of the Czech Republic - Cerveny, Daniel; Zlabek, Vladimir; Velisek, Josef; Turek, Jan; Grabic, Roman; Grabicova, Katerina; Fedorova, Ganna; Rosmus, Jan; Lepic, Pavel; Randak, Tomas (Ecotoxicology and environmental safety, 2014)
The aim of this study was to compare the contamination levels of certain important fishing grounds in the Czech Republic and to assess the health risk of consuming the fish from these localities. The assessment was performed from 2006 to 2010 in 27 fishing grounds. Within this project, 707 fish from 14 different species were sampled. The concentration of selected toxic metals (Hg, Pb, Cd) and persistent organic pollutants (POPs), such as non-dioxin-like polychlorinated biphenyls (NDL-PCBs), hexachlorocyclohexane (HCH) isomers, dichlorodiphenyltrichloroethane (DDT) and its metabolites (o,p´-DDE; p,p´-DDE; o,p´-DDD; p,p´-DDD; o,p´-DDT; p,p´-DDT) and hexachlorobenzene (HCB), were analysed in the muscle tissue of the sampled fish. Atomic absorption spectrometry (AAS) was used for the analysis of toxic metals. All of the POPs were analysed using gas chromatography with an electron capture detector (GC/ECD). Common bream (Abramis brama) was chosen as a reference fish species for the comparison of fishing grounds. Mercury was found as a major pollutant in fish flesh at all of the sampling sites. Concentrations in excess of the maximum level (ML) of mercury in the muscle tissue of fish (0.5 mg kg(-1)) were registered in 32 samples. Concentrations of other monitored toxic metals in fish muscle were low, typically below the limit of quantification (LOQ). From the tested POPs, DDTs and NDL-PCBs were found as major pollutants. ML for NDL-PCBs (ICES-6) in muscle tissue of fish (0.125 mg kg(-1)) was exceeded in 7 samples. In case of tested pesticides, concentrations in excess of the MRL were not registered.
Keywords: Animals; svaly; Spectrophotometry, Atomic; geologické sedimenty; hodnocení rizik; chemické látky znečišťující vodu; Water Pollutants, Chemical; monitorování životního prostředí; Rivers; Fishes; Hydrocarbons, Chlorinated; Muscle; Health risk; Risk Assessment; ryby; spektrofotometrie atomová; Fish; Mercury; chlorované uhlovodíky; těžké kovy; Czech Republic; řeky; Environmental Monitoring; Pesticides; Česká republika; Muscles; Geologic Sediments; zvířata; POPs; Metals, Heavy; pesticidy